Four Bosons EM Conservation Laws - Doria, R. M.; Soares, I. (JOURNAL OF ADVANCES IN PHYSICS, 2021)
Electromagnetism is expressed from two basic postulates. They are light invariance and charge conservation. At this work one extends the Maxwell scenario from macroscopic to microscopic electromagnetism by following the elementary particles electric charge microscopic behavior. It yields a triune electric charge interrelationship. Three charges {+, 0, −} be exchanged through a vector bosons quadruplet. It is called Four Bosons Electromagnetism. A systemic EM physics appears to be understood. Maxwell photon is not enough for describing the microscopic electric charge physics. An extension for electromagnetic energy is obtained. The fields quadruplet {Aµ, Uµ, Vµ±} are the porters of electromagnetic energy. They are the usual photon Aµ, massive photon Uµ and two charged photons Vµ±, A new understanding on EM phenomena has to be considered. A set determinism based on granular and collective fields is developed. A space-time evolution associated to a whole. Conservation laws are studied. The EM phenomena is enlarged to three charges interchanges to {+, 0, −}. Two novelties appear. New features on nonlinear fields acting as own sources and on electric charge physics. Properties as conservation, conduction, transmission, interaction are extended to a systemic electromagnetism. A whole conservation law for electric charge emerges from three charges interwoven. Electric charge has a systemic behavior. Although there is no Coulomb law for zero electric charge, the Four Bosons Electromagnetism contains an EM energy which provides a neutral electromagnetism. Particles with zero charge {Aµ, Uµ} are carrying EM energy. Another consideration is on EM energy being transported by four nonlinear fields. A new physicality appears. The abelian nonlinearity generates fields charges. Fields are working as own sources through mass terms, trilinear and quadrilinear interactions, spin couplings. Consequently the photon is more than being a consequence from electric charge oscillations. It is able to generate its own charge. Introduce the meaning of photonics. Thus, electric charge is no more the isolate electromagnetic source. There are another conservation laws. Fields sources appear through corresponding equations of motion, Bianchi identities, energy-momentum, Noether laws and angular momentum conservation laws. They move EM to a fields charges dependence. Together with electric charge they carry the electromagnetic flux. Supporting the Ahranov-Bohm experiment of potential fields as primitive entities.